2022
DOI: 10.1038/s41598-022-22109-z
|View full text |Cite
|
Sign up to set email alerts
|

The law of blast stress wave propagation and fracture development in soft and hard composite rock

Abstract: The process of blasting stress wave propagation and crack propagation is directly affected by the physical properties of the rock mass and internal joints in the rock. In soft and hard rock layers, the blasting process is more complicated since the blasting stress wave needs to penetrate two kinds of rocks with different physical properties and the interface between soft rock and hard rock. In this study, the modal transformation of stress waves at the interface of layered composite rock was analyzed, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Recent research addresses the topic of delays in blasting. [19,20] consider crack growth: they state that delayed initiation provides enough timing for preconditioning the surrounding rock for the neighboring blasthole. [21] considered the initiation sequence of a row of holes: one-directional initiation vs. initiating the row from the extremities towards the center: the order of ignition of blast holes is from the center to both ends of the row of blast holes can produce a more uniform size of fragmented rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research addresses the topic of delays in blasting. [19,20] consider crack growth: they state that delayed initiation provides enough timing for preconditioning the surrounding rock for the neighboring blasthole. [21] considered the initiation sequence of a row of holes: one-directional initiation vs. initiating the row from the extremities towards the center: the order of ignition of blast holes is from the center to both ends of the row of blast holes can produce a more uniform size of fragmented rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Damage zones around a single-hole blast have been studied by several researchers experimentally and using numerical models [3][4][5][6][7][8]. These studies observed that several factors influence the extent of damage zones, the main ones being the explosive strength (determined using the velocity of detonation (VOD), density, and detonation pressure) and rock mass strength (uniaxial compressive strength, tensile strength, Young's modulus, and Poisson ratio).…”
Section: Introductionmentioning
confidence: 99%
“…Layered composite rock masses with multiple parallel joints are present in many natural strata 1–4 . When the stress wave propagates through the layered composite rock masses, the wave not only undergoes direct transmission but also undergoes multiple reflections between parallel joints 5–8 .…”
Section: Introductionmentioning
confidence: 99%